ADEQUACY OF CAPITAL MARKET COMPANIES TO CPC 28 (INVESTMENT PROPERTIES) (Gestão & Regionalidade, 2018)
The convergence of Brazilian accounting standards with international accounting standards generated a series of studies directed to analysis, interpretation, verification and identification of items such: meeting standards, its cost/benefit, among other possibilities. We sought in this work to check whether the information disclosed by the publicly traded Brazilian companies on non-current assets section - Investment Property fully meet the recommended requirements in CPC 28, aiming the compliance of the information brought to market with the accounting standards used. The methodology adopted was based on the literature, by proposing a descriptive analysis with a qualitative approach of the different positions on the proposed goal. We emphasize in the analysis of data that companies which measure their assets at fair value had a higher volume of disclosure of information regarding the ones which opted for the cost. We also observed that there was a general evolution in the period analyzed about disclosures, however, due to lack of an effective standard of disclosure of the items required by the standard may be occurring comparability issues as well as difficulties in interpretation, resulting in gaps that can generate the omission of important information. Keywords: Investment property; mensuration; disclosed accounting informations.